Implementation of Load Balancing based Charging on Sensor and Non-Sensor Nodes in WSNs - Reetika, Suraj Pal (International Journal of Advanced Science and Technology, 2020)
This paper proposes a technique of load balancing and power charging to mitigate the short lifespan problem in wireless sensor networks (WSNs). Further, the load balancing based power charging technique is implemented on sensor and non-sensor types of wireless nodes to find out the best suitable type of node in WSNs. To evaluate the proposed technique, we firstly use a set the number of nodes to test its performance, and then implementation is performed on different types of nodes. Finally, the results are compared with technical parameters also called performance metrics. The performance metrics used for our work includes: such as the load balancing, execution time, energy consumption, and convergence rate.